2019
DOI: 10.1039/c9ra06785j
|View full text |Cite|
|
Sign up to set email alerts
|

Rechargeable Zn2+/Al3+ dual-ion electrochromic device with long life time utilizing dimethyl sulfoxide (DMSO)-nanocluster modified hydrogel electrolytes

Abstract: Despite recent advances in hydrogel electrolytes for flexible electrochemical energy storage, ion conductors still exhibit some major shortcomings including low ionic conductivity and short lifetimes. As such, for applications in electrochromic batteries, a transparent, highly conductive electrolyte based on a dimethyl-sulfoxide (DMSO) modified polyacrylamide (PAM) hydrogel is being developed and implemented in a dual-ion Zn 2+ /Al 3+ electrochromic device consisting of a Zn anode and WO 3 cathode.Gelation in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(24 citation statements)
references
References 62 publications
0
24
0
Order By: Relevance
“…Therefore, a novel integrated device structure of the PANI thin lm with a porous structure is expected to achieve excellent electrochemical properties. However, different from the existing work, 23,29,[47][48][49][50][51][52][53][54][55] a water-in-salt type hydrogel electrolyte lled with ZnCl 2 was developed to concurrently improve the energy storage capacity and expand the operating temperature of the device. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, a novel integrated device structure of the PANI thin lm with a porous structure is expected to achieve excellent electrochemical properties. However, different from the existing work, 23,29,[47][48][49][50][51][52][53][54][55] a water-in-salt type hydrogel electrolyte lled with ZnCl 2 was developed to concurrently improve the energy storage capacity and expand the operating temperature of the device. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The transparency of a polymeric electrolyte is a requirement for application in some electrochemical devices. 65,66 The UV-Vis spectra for the XG-based electrolytes containing of 0%, 0.1%, 0.3%, 0.5%, and 0.7 wt % of GNs are shown in Figure 4. The samples were approximately 1.03 mm thick and they were measured with a digital caliper.…”
Section: Spectroscopy In the Ultravioletvisible Regionmentioning
confidence: 99%
“…Elezzabi et al proposed a novel Zn‐PB electrochromic battery system which has good compatibility between the dynamic transparent control and the electric energy storage. [ 140 ] To find an optimum dual‐ion electrolyte, they investigated Zn 2+ electrolyte, Al 3+ /Zn 2+ , and K + /Zn 2+ dual‐ion electrolytes for comparison. They found that PB cathode in 1 m ZnSO 4 ‐KCl exhibited a fast‐self bleaching behavior, with the self‐bleaching time of 2.8 s, which was the fastest switching time reported in ZnECMs to date.…”
Section: Design and Improvement Of Advanced Ions‐based Electrochromic...mentioning
confidence: 99%